2019
DOI: 10.1097/iae.0000000000002252
|View full text |Cite
|
Sign up to set email alerts
|

Visual Function and Retinal Changes in Patients With Bipolar Disorder

Abstract: Patients with bipolar disorder present quantifiable thinning of the macular RNFL, ganglion cell layer, and inner plexiform layer, as well as in the peripapillary RNFL thickness, and increasing thinning in the inner nuclear layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 41 publications
0
37
0
2
Order By: Relevance
“…A few studies have examined RNFL thickness using OCT in SCZ and BD patients and have reported thinning of the RNFL and the inner nuclear layer in patients compared to HV.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have examined RNFL thickness using OCT in SCZ and BD patients and have reported thinning of the RNFL and the inner nuclear layer in patients compared to HV.…”
Section: Discussionmentioning
confidence: 99%
“…24 Celik et al 24 also showed that GCL-IPL volume was smaller in treatment-refractory patients compared to responsive patients. On the other hand, Garcia-Martin et al, 32 found a strong positive correlation between GCL thickness and disease duration, whereas Khalil et al 29 did not find any associations between GCC and clinical measures of disease severity or duration. No differences were observed for GCL volume between smokers and non-smokers.…”
Section: Gcl Gcl-ipl and Gcc Findingsmentioning
confidence: 93%
“…However, 5 studies reported a significant negative relationship between RNFL thickness and disease duration, 25,26,30,33,34 while 6 others did not observe a relationship. 23,24,27,29,31,32 Additionally, RNFL thinning was associated with worse clinical symptom severity in one study, 33 no association in 7 studies [24][25][26][27]29,32,34 and when stratified by recent illness episode vs non-recent illness episode or by treatment responsive vs refractory, there were no differences in RNFL thickness for the recent illness vs controls or between treatment response groups. 23,24 In order to explain these findings, Ascaso hypothesized that neuro-inflammation, which can occur during acute episodes, may increase RNFL thickness, thus masking thinning in RNFL that are seen in chronic SZ and BD patients.…”
Section: Rnfl Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…151 Therefore, the absence of more observations of total retinal thickness change in BD may be a result of masking of thinning by simultaneous thickening of other layers. 150 Newer, swept-source OCT able to image both the retina and choroid has been used to examine patients with BD, demonstrating significant thinning in the central macula, as well as in the inner temporal, nasal and inferior zones ( Table 2). 86 However, no changes in choroidal thickness were observed.…”
Section: Rnfl Changes In Bipolar Disordermentioning
confidence: 99%